The investment trend analysis in Melaka from 1995-2006 / Noratikah Abdull Khalid (Faculty of Business and Management, 2007)
The title of this research paper is The Investment Trend Analysis In Melaka From 1995-2006.The two objectives of this study are to identify the investment trend of in Melaka from year 1995-2006 and to identify factors influencing the investment trend in Melaka. The scope of this study is Melaka and concentrates on the investment trend in Melaka and the factors influencing the investment trend in Melaka. In this study, data gathered through such existing sources are called secondary data. That is they data that already exist and do not have to be collected by the research. At the end of the study, based from the information collected, several suggestions have been made for the organization to increase the investment in Melaka and also for the future research purpose.